Trajetórias escolares no ensino fundamental: estudo de uma escola pública - Sousa, Larissa Renó Gomide de [UNESP] (2015)
This paper presents the results of a study that examined the social trajectory of four students of the 3rd year of elementary school to a public school in the city of Araraquara, which had poor academic performance. This work was based on the theoretical concepts presented in the works of Pierre Bourdieu, particularly: cultural capital, social capital, economic capital, habitus and social trajectory. The work is divided into four sections: the first section presents the School Function and what is currently understood as school failure. In the second section, I present the theoretical framework and the relationship of cultural capital and school content. In the third section, I present the School trajectories in the 3rd year of elementary school students obtained through interviews with parents and / or guardians and the school evaluation means for the characterization of poor academic performance. You can associate the poor academic performance of students with low ownership capital of parents and their low enrollment. In the course of the students there, as defined Bourdieu, good cultural empty will of the parents, which reflects the academic performance of students